2017
DOI: 10.1007/s00590-017-2046-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of direct anterior, lateral, posterior and posterior-2 approaches in total hip arthroplasty: network meta-analysis

Abstract: Total hip arthroplasty (THA) is generally considered to be one of the most successful orthopedic surgical procedures. THA patients continue to experience symptoms, most commonly pain, which prevent their return to full function and activity. Possible causes include failure of fixation, instability and damage to soft tissues, associated with the trauma of the surgical procedure. Choosing the optimal surgical approach can minimize these risks and therefore improve the outcome of THA. Surgical approaches in THA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 50 publications
3
83
0
6
Order By: Relevance
“…Good maintenance of muscular structures during Watson‐Jones surgery and along minimally invasive pathways allows better functional recovery and good post‐operative proprioception 33,34 …”
Section: Discussionmentioning
confidence: 99%
“…Good maintenance of muscular structures during Watson‐Jones surgery and along minimally invasive pathways allows better functional recovery and good post‐operative proprioception 33,34 …”
Section: Discussionmentioning
confidence: 99%
“…We found statistically significant differences between DAA and PA with regards to Harris hip score at 2 weeks and 4 weeks post op. Putananon et al [ 26 ] performed a network meta-analysis that compares DAA, lateral, PA, and posterior approaches in THA. Those results showed that DAA for THA gave the best postoperative VAS and Harris hip score.…”
Section: Discussionmentioning
confidence: 99%
“…The PRISMA meta-analysis comparing direct anterior and lateral approaches similarly suggested that DAA may be associated with improved early postoperative functional rehabilitation, lower levels of perceived pain, and shorter hospitalization time [ 15 ]. A recent network meta-analysis by Putananon et al evaluated all surgical approaches for THA [ 6 ]. They suggest that a failure of fixation, instability, and damage to soft tissues, associated with the trauma of the surgical procedure are some of the reasons for post-operative pain, which prevent patients to return to full function and activity.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent systematic reviews and network meta-analysis aimed to evaluate the effectiveness of surgical approach for THA (posterior, posterior-2, anterolateral, direct lateral, and anterior). Outcome measures were the length of the incision, blood loss, operating time, length of stay, complications, gait analysis and post-operative clinical symptoms [ 6 , 7 ]. However, both reviews did not compare the acetabular cup positioning and postoperative leg length discrepancy.…”
Section: Introductionmentioning
confidence: 99%